2007
DOI: 10.1124/jpet.106.117457
|View full text |Cite
|
Sign up to set email alerts
|

Ethonafide-Induced Cytotoxicity Is Mediated by Topoisomerase II Inhibition in Prostate Cancer Cells

Abstract: Ethonafide is an anthracene-containing derivative of amonafide that belongs to the azonafide series of anticancer agents. The lack of cross-resistance in multidrug-resistant cancer cell lines and the absence of a quinone and hydroquinone moiety make ethonafide a potentially less cardiotoxic replacement for existing anthracene-containing anticancer agents. For this study, we investigated the anticancer activity and mechanism of ethonafide in human prostate cancer cell lines. Ethonafide was cytotoxic against thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 35 publications
3
13
0
Order By: Relevance
“…Ethonafide has been previously shown to stabilize both topoIIα-and topoIIβ-DNA complexes (21), however the primary DSB formation and cytotoxicity of the agent has been attributed to inhibition of topoIIα, whereas proteasomal processing of topoII-DNA covalent complex processing is more efficient in topoIIβ complexes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethonafide has been previously shown to stabilize both topoIIα-and topoIIβ-DNA complexes (21), however the primary DSB formation and cytotoxicity of the agent has been attributed to inhibition of topoIIα, whereas proteasomal processing of topoII-DNA covalent complex processing is more efficient in topoIIβ complexes.…”
Section: Discussionmentioning
confidence: 99%
“…This agent is a member of the azonafide series of anthracenebased DNA intercalating antitumor agents (20). Mechanistically, ethonafide inhibits topo II activity by stabilizing a covalent complex between topoisomerase II and DNA, known as the cleavable complex, making ethonafide a topo II poison (21). In the present study, we examined the effects of ethonafide in combination with sub-cytotoxic doses of bortezomib as a strategy to potentiate the activity of ethonafide in drug resistant myeloma cells.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, these results demonstrated that this 6-ethoxy substituted azonafide had consistent experimental anti-tumor activity against human cancers and was considered of potential to treat patients with MDR tumors. Pourpak et al [45] further demonstrated that ethonafide was active against human prostate cancer cell lines in vitro and in vivo. Importantly, ethonafide was better tolerated, with equal or greater activity than mitoxantrone in SCID mice grafted with human DU-145 prostate cancer cells.…”
Section: Preclinical In Vivo Activitymentioning
confidence: 92%
“…Further studies have shown that this agent produces DNA single and double strand breaks, DNAprotein cross-links characteristic of topo II inhibition, as well as catalytic inhibition of topo II activity [58]. Pourpak et al [45] found that the azonafide derivative ethonafide (128) inhibited topo II activity by stabilizing the enzyme-DNA complex, involving both topo II and . In addition, the compound induced a potent G2 cell cycle arrest in the human DU-145 prostate cancer cell line.…”
Section: A) Topoisomerase II Inhibitionmentioning
confidence: 98%
“…Amonafide, among other intercalating agents, has the ability to inhibit the activity of topoisomerases I and II, preventing the enzyme's capability to catalyze cleavage of DNA [31,32]. This topoisomerase activity serves as the foundation for sensitive DNA intercalation tests for non-alkylating amonafide derivatives.…”
Section: Dna Alkylation: Electrophoretic Mobility Shift Assaymentioning
confidence: 99%